Family-group names in the scale insects (Hemiptera: Sternorrhyncha: Coccoidea)—a supplement - Williams, D. J. (Zootaxa, 2013)
Williams (1969) published a list of the family-group names in the Coccoidea (scale insects) recognised at that time. The present paper supplements this earlier list and includes all nominal genera that have had family-group names based on them, including those in the earlier paper, in case it is not readily available to some workers. Nominal genera and their family-group names are listed alphabetically in catalogue form. There are now 49 families generally recognised in the scale insects, of which 16 are only known as fossils. Furthermore, 180 nominal genera have now had family-group names based on them. As stated in the 1969 list, all categories in the family group are deemed to be of co-ordinate status in nomenclature.